2012
DOI: 10.1007/s11524-011-9647-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Partnership Working in Cities in Phase IV of the WHO Healthy Cities Network

Abstract: An intersectoral partnership for health improvement is a requirement of the WHO European Healthy Cities Network of municipalities. A review was undertaken in 59 cities based on responses to a structured questionnaire covering phase IV of the network (2003)(2004)(2005)(2006)(2007)(2008). Cities usually combined formal and informal working partnerships in a pattern seen in previous phases. However, these encompassed more sectors than previously and achieved greater degrees of collaborative planning and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The focus of this collaborative action often includes bike lanes and safe public space for walking and other physical exercise, better public transport, smoke-free public spaces and other pollution reduction, and healthy and affordable housing. Evaluations of the Healthy Cities project in Europe found that an appropriate mix of distal interventions for health provides a broad and sustainable effect on population health, whereas proximal interventions (for example, health and patient education, health care) yield focused health gains (often disease, gender, and age-group specific) at relatively high cost 51 , 52 …”
Section: Successful Health Promotion In the Developing Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of this collaborative action often includes bike lanes and safe public space for walking and other physical exercise, better public transport, smoke-free public spaces and other pollution reduction, and healthy and affordable housing. Evaluations of the Healthy Cities project in Europe found that an appropriate mix of distal interventions for health provides a broad and sustainable effect on population health, whereas proximal interventions (for example, health and patient education, health care) yield focused health gains (often disease, gender, and age-group specific) at relatively high cost 51 , 52 …”
Section: Successful Health Promotion In the Developing Worldmentioning
confidence: 99%
“…Evaluations of the Healthy Cities project in Europe found that an appropriate mix of distal interventions for health provides a broad and sustainable effect on population health, whereas proximal interventions (for example, health and patient education, health care) yield focused health gains (often disease, gender, and age-group specific) at relatively high cost. 51 , 52 …”
Section: Successful Health Promotion In the Developing Worldmentioning
confidence: 99%
“…7,36 Second, the actors most likely to effectively impact on those complex arrays of determinants of health are municipalities, communities and other local partners that all have a legitimate institutional role in protecting and promoting health. This assumption is implicit in most analyses in the contributions in this volume, but very explicitly addressed by Lipp et al 37 and Whitfield et al 35 Third, an integral part of the conceptual perspective adopted by all authors is that Healthy Cities projects have a key role in generating the critical success components for city health development as outlined by Tsouros and by De Leeuw. 7 Interventions and Impact As soon as the complex and volatile field of determinants of urban health is acknowledged, combined with the strong value base of European Healthy Cities (including principles of equity, sustainability and participation), it would be clear that research design in this field is a quagmire of methodological challenges.…”
Section: Common Theoretical Assumptionsmentioning
confidence: 99%
“…21 " According to city representatives, a key success factor "is a strategically located office and a well-organized team with good management and communication skills. 22 " Most healthy cities have both formal political structures and informal working relationships with statutory, voluntary, private, and public agencies. An enduring commitment of Healthy cities to community participation and empowerment is now a core principle of Health 2020.…”
Section: Institutional Change-supporting Innovationmentioning
confidence: 99%
“…Cities have generally moved beyond the planning stage to implement collaborative projects and programs. 26 …”
Section: Institutional Change-supporting Innovationmentioning
confidence: 99%